2010
DOI: 10.3858/emm.2010.42.11.076
|View full text |Cite
|
Sign up to set email alerts
|

Suitable reference genes for relative quantification of miRNA expression in prostate cancer

Abstract: Real time quantitative PCR (qPCR) is the method of choice for miRNA expression studies. For relative quantification of miRNAs, normalization to proper reference genes is mandatory. Currently, no validated reference genes for miRNA qPCR in prostate cancer are available. In this study, the expression of four putative reference genes (hsa-miR-16, hsa-miR-130b, RNU6-2, SNORD7) was examined with regard to their use as normalizer. After SNORD7 was already shown an inappropriate reference gene in preliminary experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(61 citation statements)
references
References 45 publications
0
60
0
1
Order By: Relevance
“…Gene expression profiling has already demonstrated its effectiveness at subtyping various cancers, however miRNA profiles are equally discriminatory and can even be more informative, as changes in their expression can provide insights into the myriad of gene permutations observed in various cancer subtypes: links have indeed been made between misregulated miRNAs and the target genes that are affected, thus unraveling some of the unique gene networks involved [117]. miRNA profiles may identify cancer-specific signatures distinguishing between normal and cancerous tissue [118][119][120][121], but they can also discriminate different subtypes of a particular cancer [119,122,123].…”
Section: Mirnas As Prognostic Biomarkersmentioning
confidence: 99%
“…Gene expression profiling has already demonstrated its effectiveness at subtyping various cancers, however miRNA profiles are equally discriminatory and can even be more informative, as changes in their expression can provide insights into the myriad of gene permutations observed in various cancer subtypes: links have indeed been made between misregulated miRNAs and the target genes that are affected, thus unraveling some of the unique gene networks involved [117]. miRNA profiles may identify cancer-specific signatures distinguishing between normal and cancerous tissue [118][119][120][121], but they can also discriminate different subtypes of a particular cancer [119,122,123].…”
Section: Mirnas As Prognostic Biomarkersmentioning
confidence: 99%
“…In some studies, its decrease in tissue samples harvested from cancer patients, while in our study similar to those reported by Mahn et al [30] for serum samples, though not statistically significant, increased plasma miRNA levels were observed in serum samples. [31][32][33] AUCs were calculated based on ROC curves drawn using f/T PSA data obtained from PCa 1, and PCa 2 groups (0.628). Decreases in miR-25-3p, miR-125b-5p, miR-194-5p, and miR203a expression levels which demonstrated significant foldchange were seen in PCa 2 group relative to PCa 1 group.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors observed increased, while others decreased expressions of miR-125b in PCa patients. [25,28,29,[31][32][33][34][36][37][38][39] Mitchell et al [22] compared miRNA expressions in serum samples of the patients with metastatic PCa, and control patients using qRT-PCR method, and reported higher miR-125b expression levels in PCa patients. Özen et al [36] , compared expressions of miRNA in benign, and PCa tissues, and observed lower miR-125b expressions in localized prostate cancer tissue.…”
Section: Discussionmentioning
confidence: 99%
“…RNA prepared from the reference cell lines or PNF was included in every reaction plate, and every sample was analyzed using probes for specific miRNA genes and the endogenous reference RNA RNU6B (U6 small nuclear RNA 2). To confirm the relative miRNA expression measurements, we also performed calculations using alternative reference genes [39]. Relative miR-145 expression values using the U6 small nuclear RNA 2 gene, miR-130b and the geometric mean of both reference genes are presented in Table S1.…”
Section: Quantitative Real-time Pcrmentioning
confidence: 99%